Cytogenetic analysis of three sympatric Gymnotus species (Teleostei: Gymnotidae) from the Fundo Stream, MG, Brazil - Lacerda, Maria Conceição Vieira [UNESP]; Maistro, Edson Luis [UNESP] (International Society of Cytology, 2007)
Three sympatric species of Gymnotus from the Fundo stream, a small tributary of the Sapucai river, Minas Gerais State, Brazil, were studied in relation to their karyology. Gymnotus sylvius presented 2n=40 chromosomes (36 m/sm+4 st/a), Gymnotus sp. presented 2n=50 (26 m/sm+ 24 st/a) and Gymnotus paraguensis had 2n=54 (50 m/sm+4 st/a). C-banding demonstrated positively stained heterochromatic blocks in the centromeric position of few chromosomes on G. sylvius and in the centromeric region of all chromosomes on G. paraguensis samples. The nucleolus organizer region (NOR) was located on the short arm of one st chromosome pair in G. sylvius and Gymnotus sp., and in the interstitial position on the short arm of the pair number one and below the centromere on a third chromosome on G. paraguensis. The cytogenetic data obtained indicate that Gymnotus sp. represent a new Gymnotus specie with a karyotypic constitution never observed on others species from this genus. Some aspects related to the chromosome diversification of these Gymnotus are discussed. © 2007 The Japan Mendel Society.
Keywords: C-banding; Gymnotus paraguensis; Gymnotus sp.; Gymnotus sylvius; NOR-banding; Gymnotidae; Gymnotus; Teleostei